2020
DOI: 10.1093/gerona/glaa215
|View full text |Cite
|
Sign up to set email alerts
|

17α-Estradiol Modulates IGF1 and Hepatic Gene Expression in a Sex-Specific Manner

Abstract: Aging is the greatest risk factor for most chronic diseases. The somatotropic axis is one of most conserved biological pathways that regulates aging across species. 17α-estradiol (17α-E2), a diastereomer of 17β-estradiol (17β-E2), was recently found to elicit health benefits, including improved insulin-sensitivity, and extend longevity exclusively in male mice. Given that 17β-E2 is known to modulate somatotropic signaling in females through actions in the pituitary and liver, we hypothesized that 17α-E2 may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 50 publications
3
12
1
Order By: Relevance
“…However, the dose of 17α-E2 used in the vast majority of these studies, does not induce dramatic feminization of the sex hormone profiles in male mice ( Stout et al, 2017b ), which leads us to speculate that 17a-E2 is acting in a direct manner through ERα rather than indirectly through androgen modulation. Furthermore, studies in male rodents ( Livingstone et al, 2015 ; Dowman et al, 2013 ) and humans Wei et al, 2019 demonstrate that 5α-reductase inhibition or deficiency increases insulin resistance and hepatic steatosis and fibrosis, which are contradictory to the effects of 17α-E2 treatment in all of our studies utilizing male mice ( Stout et al, 2017b ; Steyn et al, 2018 ; Miller, 2020 ; Sidhom et al, 2020 ). Despite these contrasting observations, the studies by Garratt et al do provide important insights into the interconnected and underappreciated relationship between androgen- and estrogen-signaling pathways and their roles in metabolism and aging.…”
Section: Discussionmentioning
confidence: 61%
“…However, the dose of 17α-E2 used in the vast majority of these studies, does not induce dramatic feminization of the sex hormone profiles in male mice ( Stout et al, 2017b ), which leads us to speculate that 17a-E2 is acting in a direct manner through ERα rather than indirectly through androgen modulation. Furthermore, studies in male rodents ( Livingstone et al, 2015 ; Dowman et al, 2013 ) and humans Wei et al, 2019 demonstrate that 5α-reductase inhibition or deficiency increases insulin resistance and hepatic steatosis and fibrosis, which are contradictory to the effects of 17α-E2 treatment in all of our studies utilizing male mice ( Stout et al, 2017b ; Steyn et al, 2018 ; Miller, 2020 ; Sidhom et al, 2020 ). Despite these contrasting observations, the studies by Garratt et al do provide important insights into the interconnected and underappreciated relationship between androgen- and estrogen-signaling pathways and their roles in metabolism and aging.…”
Section: Discussionmentioning
confidence: 61%
“…These sex-dependent differences in gene expression are due, in part, to differential actions of the GH pattern on STAT5 DNA binding to gene promoters, as well as STAT5-dependent alteration in DNA methylation patterns [24,28,29]. In addition, estrogens regulate hepatic gene expression (including IGF1) dependent and independent of alterations in GH release [30,31]. Therefore, with respect to understanding the role GH plays on liver metabolism, caution should be used when extrapolating findings between males and females.…”
Section: Metabolic Actions Of Gh/ghr Can Be Mediated By Multiple Intracellular Signaling Pathwaysmentioning
confidence: 99%
“…As indicated above, GH-mediated lipolysis generates NEFA, which serves as a substrate for mitochondrial β (fatty acid) oxidation and ATP generation. In acromegalic subjects, hepatic lipid content is low and is associated with an increase in hepatic ATP synthesis rate as assessed by 31 P/ 1 H-7-T MR spectroscopy [171]. In addition, aHepGHRkd mice under basal conditions suppress the hepatic expression of carnitine palmitoyltransferase 1A (Cpt1a), independent of changes NEFA levels, or enhanced hepatic insulin signaling [59].…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…Treatment of mice with Estradiol 17 alpha (17αE2; a weakly estrogenic compound, distinct from the main female sex hormone, estradiol 17 beta) produces health benefits such as improved insulin sensitivity and extends longevity in males but not in females [ 59 ]. We found that treatment with 17αE2 increased hepatic IGF-I production exclusively in males [ 60 ]. Surprisingly, this effect did not involve modifications of the pattern of GH release or “feminization” of the hepatic transcriptional profile.…”
Section: Involvement Of the Somatotropic Axis In Sexually Dimorphic Effects Of Antiaging Interventionsmentioning
confidence: 99%
“…Surprisingly, this effect did not involve modifications of the pattern of GH release or “feminization” of the hepatic transcriptional profile. However, this effect of 17αE2 on IGF-I production was GH-dependent since it was not elicited in GH-resistant Ghr-/- mice [ 60 ]. Apparently, anti-aging effects of 17αE2 in male mice are GH-dependent and involve alterations in IGF-I, but not GH dynamics.…”
Section: Involvement Of the Somatotropic Axis In Sexually Dimorphic Effects Of Antiaging Interventionsmentioning
confidence: 99%